Agri-environmental subsidies and the National Rural Development Plan - Gyarmati, Ágnes (Acta Agraria Debreceniensis, 2006)
The financing of agri-environmental target programs which is a prominent area in the EU became possible during the implementation and successful operation of the National Agricultural Environment Protection Program (NAPP) launched in 2002. Through this program we gained experience in the field agri-environmental measures which are financed from the Guidance Section of European Agricultural and Guarantee Fund in the European Union. The agri-environmental measures which are included in the National Rural Development Plan (NRDP) were implemented in Hungary in the fall of 2004 when the farmers handed in their application after the publishing of the related law. The NAPP financing is still active, but not significant since most farmers have chosen NRDP measures.We are examining the experience of the above programs after studying some theoretical aspects of the agricultural economics and the EU laws. We try to analyse the most important experiences of NAPP including the legal background, news opportunities yielded by target programs, the financing, organisation, and institutional background. We will present the results taking into consideration the data of the winning applicants.